GERAKAN SOSIAL HIZMET MUHAMMAD FETHULLAH GÜLEN DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM DI INDONESIA - Rian Hidayat (TASAMUH, 2020)
ABSTRACT This research is a descriptive qualitative research, using interviews, observation, and literature documentation as the data collection process. The data analysis techniques used are data reduction, data presentation, conclusion, and verification. To test the validity of the data in this study, the triangulation technique was used. The findings of this research are: First, when social, economic, and political opportunities emerged to develop during the Turgut Ozal era, hizmet made the best use of this atmosphere of openness. Hizmet founded schools, dersane (home learning), student dormitories, hospitals, entrepreneurial institutions, newspapers, magazines, and others. Second, Fethullah Gülen made three concepts in mobilizing Turkish society to engage in peaceful movements, namely through: hizmet (providing services to religion and the state); himmet (donating funds or doing a good job) and sincerity (seeking the pleasure of Allah in every action taken). In the formation of this service network, they each build a joint effort to achieve the goals of this movement in the framework of raising funds, creating local businesses with the aim of spreading the teachings of this movement as well as building jobs. Third, the process of cultural framing of the hizmet movement can be read in the focus of this movement in the fields of da'wah and education. The hizmet movement has established educational institutions and operates approximately 1,000 schools in 130 countries, including in Indonesia. There are hizmet schools in several cities, such as in Depok, Semarang, Tangerang, Jogjakarta, Bandung, Sragen, Banua, Aceh, Bogor and Medan. Keywords: Social Movement, Hizmet, Fethullah Gülen, Education ABSTRAK Penelitian ini merupakan penelitian kualitatif deskriptif, dalam proses pengambilan data menggunakan wawancara, observasi, dan dokumentasi pustaka. Sedangkan teknik analisis data menggunakan reduksi data, sajian data, kesimpulan, dan verifikasi, sedangkan untuk menguji keabsahan data dalam penelitian ini dipergunakan teknik triangulasi. Temuan dari penelitian ini, yaitu: Pertama, saat peluang secara sosial, ekonomi, dan politik muncul untuk berkembang di masa Turgut Ozal, hizmet memanfaatkan atmosfer keterbukaan itu dengan sebaik-baiknya. Hizmet mendirikan sekolah, dersane, asrama mahasiswa, rumah sakit, institusi pengusaha, koran, majalah, dan lain-lain. Kedua, Fethullah Gülen membuat tiga konsep dalam memobilisasi masyarakat Turki untuk terlibat dalam gerakan damai, yaitu melalui: hizmet (memberikan pelayanan kepada agama dan negara); himmet (memberikan sumbangsih dana atau dengan mengerjakan pekerjaan dengan baik) dan ikhlas (mencari ridha Allah dalam setiap tindakan yang dilakukan). Pembentukan jaringan pelayanan ini mereka satu sama lain membangun sebuah usaha bersama demi tercapainya tujuan dari gerakan ini dalam rangka pengumpulan dana, pembuatan usaha-usaha lokal dengan tujuan menyebarkan ajaran gerakan ini sekaligus membangun lapangan kerja. Ketiga, proses pembingkaian kultural gerakan hizmet bisa dibaca pada fokus gerakan ini dalam bidang dakwah dan pendidikan. Gerakan hizmet sudah mendirikan lembaga-lembaga pendidikan dan mengoperasikan kurang lebih 1.000 sekolah di 130 negara, termasuk di Indonesia terdapat sekolah hizmet di beberapa kota, seperti di Depok, Semarang, Tangerang, Jogjakarta, Bandung, Sragen, Banua, Aceh, Bogor, dan Medan. Kata Kunci: Gerakan Sosial, Hizmet, Fethullah Gülen, Pendidikan